+0  
 
0
71
1
avatar+80 

Rewrite the expression g^4 + 12g^2 + 9 in the form c(g^2 + p)^2 + q. What is q

 Dec 26, 2018
 #1
avatar+98005 
+1

Rewrite the expression g^4 + 12g^2 + 9 in the form c(g^2 + p)^2 + q. What is q

 

g^4 + 12g^2 + 9       take 1/2 of 2  = 6....square it  36....add and subtract it

 

g^4 + 12g^2 + 36  + 9 - 36

 

Factor the first three terms........simplify the rest

 

(g^2 + 6)^2  -  27

 

c = 1

 

p = 6

 

q = -27

 

 

cool cool cool

 Dec 26, 2018

8 Online Users